Estructura del tallo y ontogenia de los diafragmas caulinos en Phytolacca icosandra L. - Camacho Granados, Lucía (1979)
In Phytolacca icosandra the formation of cauline diaphragms is the result of the desintegration of the medular tissue when anomalous secondary growth begins. The presence of a diaphragm in these plants is possibly due to the necessity of reducing stem weight, the early initiation of secondary growth, and the accelerated growth of this species.